Peningkatan Keterampilan Pengolahan Frozen Food Dalam Rangka Menumbuhkan Perekonomian dan Mewujudkan Ketahanan Pangan - Edi Fitriana Afriza; Rd. Roro Suci Nurdianti; Sri Hardianti Sartika; Betanika Nila Nirbita (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The impacts of the COVID-19 pandemic has affected significant changes to people's consumption patterns, notably family food needs. The policy of restricting activities imposed by the government has switched family consumption patterns to instant food. One of them is Frozen Food. Frozen Food is a type of food processed food products increasingly favoured by the public during the pandemic. This is due to its durability and practicality to consume. The non-productive groups of Beneficiary Families (Kelompok Penerima Manfaat) of the Family Hope Program or Program Keluarga Harapan (PKH) in Cinunjang and Giriwangi Villages, Gunung Tanjung District, Tasikmalaya Regency experienced problems in obtaining food supplies during the pandemic. This occurred because majority of them still rely on the social assistance of central government to support their economic life. The activities of the current program encompassed three stages, namely preparation, briefing, and implementation and evaluation. This program adopted the andragogy approach. Practically, the activities were performed to 15 Hope Family Program groups in Cinunjang and Giriwangi. They were trained to have better knowledge in understanding and practicing how to produce frozen food in nuggets. Also, they were guided to promote it commercially as a new prospective food business during the pandemic. The results of training program run effectively. The participants were successfully be able to implement the training materials productively and independently.